PENGARUH PELATIHAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA PERAWAT RSUD DORAK DI KABUPATEN KEPULAUAN MERANTI - Meri Andesta; Nuryanti -; Taufiqurrahman - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at the Meranti Islands Regency Hospital Dorak Jl.Dorak. This study aims to determine how the Effect of Training and organizational commitment simultaneously or partially on the performance of nurses in hospitals Dorak Meranti Islands Regency. As for the population in this study were all nurses in hospitals Dorak Meranti Islands Regency, amounting to 85 people and the whole population sample were calculated using the formula of Slovin sample as respondents, the method of analysis used is descriptive and quantitative analysis with SPSS Version 20. From the results of simultaneous testing (F test) showed that the independent variables studied (Training and organizational commitment) has a positive and significant effect on the variable (performance of nurses). The results of the testing that has been done, the partial regression test (t test) showed that each of the variables studied bebes (Training And Organizational Commitment) has a positive and significant impact on the dependent variable (performance Nurses).Keywords: Training, Organizational Commitment and Performance Nurse